Identification and Validation of a Stromal EMT Related LncRNA Signature as a Potential Marker to Predict Bladder Cancer Outcome - Du, YiHeng; Wang, Bo; Jiang, Xiang; Cao, Jin; Yu, Jiang; Wang, Yi; Wang, XiZhi; Liu, HaiTao (Frontiers in Oncology, 2021)
Bladder cancer (BLCA) has become one of the most common malignant tumors in the genitourinary system. BLCA is one of the tumors considered suitable for immunotherapy because of the large proportion of immune cells in TME. Epithelial to mesenchymal transition (EMT) is closely related to tumor immunity through its crosstalk with immune cells. A recent study validated that EMT-related genes were mainly expressed by stromal cells and could influence immunotherapy responsiveness. Stromal EMT-related gene signature was also demonstrated to affect the prognosis of multiple tumors, including BLCA. To further explore the prognostic roles of stromal components, we performed a comprehensive analysis of LncRNAs closely associated with stromal EMT-related genes in the TCGA BLCA cohort. We identified a signature including five stromal EMT gene-related LncRNAs that showed significant prognostic value for BLCA patients. By the CIBERSORT and MCP-COUNTER algorithm, we found the signature was markedly correlated with infiltrated immune cells and stromal components of the tumor microenvironment, which may further influence patient's responsiveness to immune checkpoint blockade therapy. Through immunohistochemical analysis, we confirmed the correlation of the signature with macrophages M2 and CAFs. Meanwhile, key genes related to these LncRNAs, including VIM, MMP2, were also differentially expressed majorly in the stromal components concerning the signature. Our research confirmed the prognostic and immune-associated role of stromal EMT-related LncRNAs. Meantime, we further confirmed that EMT-related genes were mainly expressed in stromal components. Targeting these LncRNAs as well as their related stromal EMT genes may provide potential therapeutic targets for BLCA immunotherapy and precision medicine.